An Empirical Study on Factors influencing Apparel Brand Loyalty among Malaysian Women - Jayanty KUPPUSAMY; Ajitha ANGUSAMY; Kavitha BALAKRISHNAN; Kai Ting TEO (Communications of International Proceedings, 2020)
The apparel industry is a very competitive industry. In Malaysia, the apparel industry consists of players from both the international and local brand. Due to the high competition, it is critical to attract and retain loyal customers. One way is to create brand loyalty where the customers will not switch to a different brand easily. Therefore, the main purpose of this research is to study the factors influencing apparel brand loyalty. The target respondents are the Malaysia women. The factors studied included price, product quality, service quality, uncontrolled communication and store environment. The data was collected from 200 respondents through the survey method. The multiple regression analysis identified that all the factors studied contribute to brand loyalty. Therefore, the retailers need to ensure these factors are considered and matched with the customer expectations to create brand loyalty.
Keywords: brand loyalty; product quality; service quality; store environment